Mechanisms and regulation of iron trafficking across the capillary endothelial cells of the blood-brain barrier - McCarthy, Ryan C.; Kosman, Daniel J. (Frontiers in Molecular Neuroscience, 2015)
The transcellular trafficking of iron from the blood into the brain interstitium depends on iron uptake proteins in the apical membrane of brain microvascular capillary endothelial cells and efflux proteins at the basolateral, abluminal membrane. In this review, we discuss the three mechanisms by which these cells take-up iron from the blood and the sole mechanism by which they efflux this iron into the abluminal space. We then focus on the regulation of this efflux pathway by exocrine factors that are released from neighboring astrocytes. Also discussed are the cytokines secreted by capillary cells that regulate the expression of these glial cell signals. Among the interstitial factors that regulate iron efflux into the brain is the amyloid precursor protein. The role of this amyliodogenic species in brain iron metabolism is discussed. Last, we speculate on the potential relationship between iron transport at the blood-brain barrier and neurological disorders associated with iron mismanagement.